Public Perception And Understanding Of Profit Sharing In Islamic Banks (Case Study In Karangtalun Village, Kalidawir Subdistrict, Tulungagung Regency) - Elwi Yuda Laksana; Eka Wahyu Hestya Budianto (WADIAH, 2025)
This study aims to understand the perceptions and understanding of the people in Karangtalun Village regarding the profit-sharing concept in Islamic Banks. This research uses a qualitative approach, collecting data from the community in Karangtalun Village. Data collection methods include observation, interviews, and documentation. The data analysis method consists of three main stages: data reduction, data presentation, and conclusion drawing. Most people in Karangtalun Village have a negative perception of profit-sharing, with doubts about its validity, viewing it similarly to interest; only a few individuals, such as academics and religious figures, hold a positive view of profit-sharing in Islamic banks. Similarly, the community’s understanding is still limited; most people do not fully grasp the concept of profit-sharing or its mechanism in detail, with many still believing that profit-sharing is the same as interest. In contrast, academics and religious leaders tend to have a better understanding of Islamic bank profit- sharing. The negative perception and lack of understanding of profit-sharing are due to several factors, such as the lack of experience with profit-sharing, individual backgrounds, and unclear information. These factors contribute to the community’s less favorable perception and understanding of profit- sharing.